Leveraging Rugby Event to Enhance The Economic Development of MSMEs in Garut - Mochamad Malik Akbar Rohandi; Eka Tresna Gumelar; Cici Cintyawati; Rezi Muhamad Taufik Permana (Jurnal Manajemen Bisnis Performa, 2022)
Since the past several decades, sports are increasingly in demand by people in the world, including the Indonesian. This is supported by the large number of sports activities held in in Indonesia, like Rugby sporting event. Rugby is a sport and needs to be introduced further to the public considering its enormous benefits in building positive character for young people. The purpose of this research is to promote the sport of Rugby in Indonesia, especially in West Java, as well as to stimulate the economy of Micro, Small, and Medium Enterprises (MSMEs) around the area of this sporting event through training programs. This research used participatory techniques through mentoring and training methods, assistance to PRUI West Java from and during the event and training to MSMEs around the event area. This research uses descriptive qualitative approach by utilizing the primary data obtained from the participatory technique. The results of this study indicate that with this Rugby sport activity, MSMEs can obtain economic benefits in the form of an increase in income by 56.37%. This event then became a medium for MSMEs to promote and sell their products to the visitors of this event.